2019
DOI: 10.1371/journal.pone.0217213
|View full text |Cite
|
Sign up to set email alerts
|

Is risk-stratified breast cancer screening economically efficient in Germany?

Abstract: Objectives Risk stratification has so far been evaluated under the assumption that women fully adhere to screening recommendations. However, the participation in German cancer screening programs remains low at 54%. The question arises whether risk-stratified screening is economically efficient under the assumption that adherence is not perfect. Method We have adapted a micro-simulation Markov model to the German context. Annual, biennial, and triennial routine screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…All studies, except for Arnold et al, 31 reported significant QALY/LYG for RBS strategies. Among the articles 32,33,36 that incorporated risk‐stratification cost, Gray et al 33 and Sun et al 36 reported no cost‐savings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies, except for Arnold et al, 31 reported significant QALY/LYG for RBS strategies. Among the articles 32,33,36 that incorporated risk‐stratification cost, Gray et al 33 and Sun et al 36 reported no cost‐savings.…”
Section: Resultsmentioning
confidence: 99%
“…All studies are either from upper‐middle‐income (China and Spain) or high‐income countries (World Bank classification). Most of the studies adopted the payer perspective (government taxation and/or health insurance financing) 13,17,18,21,31‐34 . The societal perspective, which in addition to direct medical costs, also considers the cost of care that do not fall on the payer's perspective (OOPs, caregiver effects and patient time) and the indirect costs (productivity losses related to morbidity and mortality) are broadly neglected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite potential cultural differences in preferences for health states between the German and the British population, we believe that the British value set is more useful to value health states in our sample. Additionally, we want to point out that using the British value set in a non-UK-based study is a frequently implemented approach [46][47][48][49].…”
Section: Measurement Of Effects: Eq-5d-3l and Qalymentioning
confidence: 99%